Another look at ‘peak and decline’ carbon emissions countries: Which ones have decoupled per capita emissions from GDP and how? - Brantley Liddle; Steven Parker (Global Environmental Change Advances)
Two recent papers identified a number of countries that have sustained reductions in carbon emissions. We first take a closer look at per capita emissions trends to settle on 24 ‘peak and decline’ carbon emissions countries. Then, we use a set of methods drawn from both economics and the larger energy/climate literature (i) to determine which of those countries have decoupled emissions from GDP, such that emissions and GDP are negatively associated/correlated, and (ii) to uncover how those decoupling countries achieved such a state. Only 15 countries actually have decoupled carbon emissions from GDP. They have done so by both reducing their energy consumption and decarbonizing their energy systems. And these decoupling countries have decarbonized largely by increasing both the share of energy services that are delivered via electricity and the share of nonfossil fuels used to generate that electricity. We conclude that sustaining declining carbon emissions will depend mainly on additional decarbonization, which itself will require further electrification of energy services.